Olsalazine versus placebo in the treatment of mild to moderate ulcerative colitis: a randomised double blind trial. Issue 10 (October 1989) - Feurle, G E; Theuer, D; Velasco, S; Barry, B A; Wördehoff, D; Sommer, A; Jantschek, G; Kruis, W
Abstract : The effect of olsalazine, an analogue of sulphasalazine, consisting of two molecules 5-aminosalicylic acid linked by an azobond has been investigated for the treatment of ulcerative colitis. In a randomised double blind trial we compared 2 g olsalazine with placebo for four weeks. Of the 105 patients, with mild to moderate ulcerative colitis, entered in the trial 52 received olsalazine, and 53 placebo. Treatment had to be terminated prematurely because of untoward effects of olsalazine (mainly diarrhoea) in three patients and treatment failure--that is, increased rectal bleeding in four patients (olsalazine group: one placebo group: three). After four weeks' treatment, a statistically significant improvement in the endoscopic findings in rectum and a positive trend in the reduction of rectal mucus and blood discharge was observed in the patients treated with olsalazine. No statistically significant difference was found for other factors, including stool frequency, consistency, urge to defecate, abdominal pain, and biopsy findings. A comparison between these clinical and endoscopic parameters at study entry and those at study completion (within drug evaluation) showed significant improvement in six of 10 parameters during treatment with olsalazine and in two of 10 during placebo treatment. This difference suggests the significant effect of olsalazine. We conclude that 2 g olsalazine was tolerated as well as placebo, apart from causing diarrhoea in some patients and was slightly superior to placebo during four weeks' treatment of mild to moderate ulcerative colitis. A study with 3 or 4 g olsalazine per day may show a more definite effect.